Development of a biocompatible hydrogel based on native temporomandibular joint extracellular matrix powder - Trindade, Daniela (2022)
The temporomandibular joint disc (TMJd) is an avascular and fibrocartilaginous tissue with low regeneration capacities. To date there is no permanent solution upon its damage. So, our group hypothesise that the combination of a synthetic material [poly(ethylene glycol) diacrylate, PEGDA] and decellularised matrices may be the answer, since it has the advantage of retaining extracellular matrix (ECM) components. For this purpose, lamb TMJd were decellularised with ethanol (96%)/ acetone (99.5%) followed by an analysis to the ECM obtained. Afterwards, different concentrations of ECM powder were added to the PEGDA to obtain hybrid hydrogels. Their swelling capacities and mechanical behaviour (hydrated or dry) were assessed. Results show a reduction of the proteoglycans in the disc, except in the posterior region. Dried hydrogels with 2% ECM powder are the ones with the closer compressive modulus to the native disc, along with greater viscoelastic capacity, representing a possible approach to a TMJd replacement.